2004
DOI: 10.1158/1078-0432.ccr-04-1245
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Epidermal Growth Factor Receptor Mutations with Complex Patterns in Non–Small Cell Lung Cancers Related to Gefitinib Responsiveness in Taiwan

Abstract: Purpose: Epidermal growth factor receptor (EGFR) mutations related to gefitinib responsiveness in non-small cell lung cancer have been found recently. Detection of EGFR mutations has become an important issue for therapeutic decision-making in non-small cell lung cancer.Experimental Design: Mutational analysis of the kinase domain of EGFR coding sequence was done on 101 fresh frozen tumor tissues from patients without prior gefitinib treatment and 16 paraffin-embedded tumor tissues from patients treated with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

56
412
6
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 501 publications
(479 citation statements)
references
References 22 publications
56
412
6
5
Order By: Relevance
“…This case suggests that in vitro sensitivity to gefitinib correlates with distinct clinical responsiveness to gefitinib in various types of EGFR mutations. [4][5][6][7][8][9][10] however, in in-vitro studies, some of these mutations (including S768I) conferred less sensitivity to gefitinib than the two major types of mutations, and even its wild-type counterpart. 11 Because of lower frequency of these novel mutations, clinical information of their relationships with drug responsiveness is very limited so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This case suggests that in vitro sensitivity to gefitinib correlates with distinct clinical responsiveness to gefitinib in various types of EGFR mutations. [4][5][6][7][8][9][10] however, in in-vitro studies, some of these mutations (including S768I) conferred less sensitivity to gefitinib than the two major types of mutations, and even its wild-type counterpart. 11 Because of lower frequency of these novel mutations, clinical information of their relationships with drug responsiveness is very limited so far.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10]13 Although multiple studies have shown striking correlation between these factors, [1][2][3]5,[8][9][10] a correlative study in a large clinical phase III trial, BR21, showed no significant association of EGFR mutations with responsiveness to erlotinib or with survival after this agent was administered. 13 One possible reason for such a discrepancy could be that different mutations have different effects on response to EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…These phenotypic features had already been marked as clinical predictors of response to TKIs before the discovery of the mutations (Fukuoka et al, 2003;Kris et al, 2003). The prevalence of EGFR mutations varies by ethnicity with ranges from 20-40% in Asian populations (Huang et al, 2004;Kosaka et al, 2004;Han et al, 2005;Shigematsu et al, 2005;Tokumo et al, 2005) to 5-20% among Caucasians (Cappuzzo et al, 2005;Marchetti et al, 2005).…”
Section: Egfr Mutations As Biomarkersmentioning
confidence: 99%
“…The overall response rates were as high as 80% in patients harboring mutations compared with p10% in patients with wildtype EGFR (Huang et al, 2004;Lynch et al, 2004;Mu et al, 2004;Paez et al, 2004;Pao et al, 2004; Sasaki et al, 2006;Kosaka et al, 2007;Yoshida et al, 2007;see Gazdar, 2009).…”
Section: Egfr Mutations As Biomarkersmentioning
confidence: 99%
“…The other is a point mutation in exon 21 (2573T>G) that results in substitution of leucine by arginine at codon 858 (L858R). [4][5][6][7][8][9][10] Other much less common mutations have also been described in exons 18, 20, and 21.…”
mentioning
confidence: 99%